TTV-INFECTION: CLINICAL, EPIDEMIOLOGICAL AND DIAGNOSTIC ASPECTS - T. Y. Chernobrovkina; O. S. Litvinova; Y. D. Yankovskaya (Архивъ внутренней медицины, 2016)
Following article based on the literature and our own observations presents a brief analytical review covering clinical and epidemiological characteristics of hepatitis associated with TT virus, as well as modern methods of diagnosis and approach to the treatment of infectious diseases. The clinical observation showed symptoms of acute inflammation of the liver caused by TTV-infection. Characteristics of epidemiological anamnesis confirms that besides the main parenteral mechanism there is also a fecal-oral mechanism of infection TT virus. Following observation verifies a longterm persistence of TT virus in the body and complete absence of spontaneous elimination.